Sprayed biodegradable liquid film improved the freezing tolerance of cv. Cabernet Sauvignon by up-regulating soluble protein and carbohydrate levels and alleviating oxidative damage - Han, Xing; Yao, Fei; Xue, Ting-ting; Wang, Zhi-lei; Wang, Ying; Cao, Xiao; Hui, Miao; Wu, Dong; Li, Yi-han; Wang, Hua; Li, Hua (Frontiers in Plant Science, 2022)
Most cultivars of Vitis vinifera L. are very sensitive to cold. As an exogenous protectant, Biodegradable Liquid Film (BLF) is considered to protect wine grapes over winter. This study aimed to reveal the physiological and biochemical mechanisms of BLF regulating the freezing tolerance of wine grapes. Groups of ten-year-old vines (Cabernet Sauvignon) were sprayed with BLF in November 2020 and 2021, or left untreated as a control treatment, and field plant mortality after overwintering were investigated. Branch samples were collected monthly for determination of biochemical indicators. Dormant two-year-old cuttings (Cabernet Sauvignon) were also used for the determination of relative expression levels of key genes. The results showed that the application of BLF reduced the branch semi-lethal temperature in January and February samples compared with control, and reduced the mortality of above-ground parts, branches and buds. The physiological status of shoots was greatly affected by the climatic conditions of the year, but BLF treatment increased the levels of soluble protein and soluble sugar, and also decreased the content of superoxide anion and malondialdehyde at most sampling times. Correlation analysis showed that the differences in freezing tolerance between BLF and CK vines were mainly related to POD activity, soluble sugar, reducing sugar and starch content. Low temperature stress activated the over expression of ICE1, CBF1, and CBF3, especially for 12h. BLF treatment significantly increased the expression levels of CBF1 and CBF3 under low temperature stress.